Acute flaccid paralysis: An approach to diagnosis (Health Renaissance, 2017)
Acute flaccid paralysis (AFP) is a common presentation to the emergency department and can present with paralysis of single to several limbs. Here is a case with AFP presented to highlight the approach to diagnosis. A 25 years male who recently returned from Malaysia presented to the emergency ward with acute onset of paralysis for two days which was progressive and was gradually involving the chest muscles as well. He had a history of loose mucoid stool since 4-5 days but there were no rashes or exanthema in the body. On complete examination, apart from diminished power in all the limbs, there were no other positive findings. He was started on expectant management and no other medications except multivitamins were prescribed. Patient was discharged home on patient party’s request and on follow-up after 14 days, patient's had improved.Health Renaissance 2015;13(2): 164-169